THE IMPACT OF INFORMATION ASYMMETRY AND FINANCIALPERFORMANCE ON EARNINGS MANAGEMENT BY USING GOOD CORPORATE GOVERNANCE AS MODERATING VARIABLE - Chandra Leonardo Dapinci Tambunan; Atik Djajanti; Heri Irawan (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
This study was conducted to determine the effect of information asymmetry and financial performance on earnings management by using Good Corporate Governance (GCG) as a moderating variable. Financial performance in this study was measured by profitability and solvability. The type of data used in this study is quantitative data in the form of data in the form of numbers in the form of financial statements on manufacturing companies. The sample involved in this study comprises of 41 manufacturing companies listed on the Indonesia Stock Exchange (BEI); covering 123 firm-year observations from the fiscal years 2018 to 2020. The research hypotheses were tested using Moderated Regression Analysis. The result of this study found that: 1) asymmetry information had significant positive effect to earnings management; 2) profitability had significant positive effect to earnings management; 3) solvability had no significant negative effect to earnings management; 4) GCG can reduce the positive effect of asymmetry information to earnings management; 5) GCG cannot reduce the positive effect of profitability to earnings management; and 6) GCG cannot strengthen the negative effect of solvability to earnings management.